2004
DOI: 10.1016/j.femsle.2004.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Freeze tolerance of the yeastTorulaspora delbrueckii: cellular and biochemical basis

Abstract: The freeze stress responses to prolonged storage at -20 degrees C in Torulaspora delbrueckii PYCC5323 were investigated. In this yeast, no loss of cell viability was observed for at least 120 days during freezing at -20 degrees C, whereas a loss of 80% was observed in a commercial baker's yeast after 15 days. In the former strain, freeze resistance was dependent on an adaptation process. The primary cell target of freeze stress was the plasma membrane, preservation of its integrity being related with a lower i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…The biotechnological interest in Torulaspora delbrueckii has increased in recent years due to its particularly high freezing and osmotic tolerance (4,5,46). These features made this yeast species a candidate of potential value for the baking industry.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The biotechnological interest in Torulaspora delbrueckii has increased in recent years due to its particularly high freezing and osmotic tolerance (4,5,46). These features made this yeast species a candidate of potential value for the baking industry.…”
Section: Resultsmentioning
confidence: 99%
“…Or is this yeast more comparable to S. cerevisiae as is suggested by their similar sugar utilizations patterns (7)? Evidently, it would be important to continue the characterization of T. delbrueckii strains, as their biotechnological potential has already been established (5,7,46). It is clear that answers to these questions may only arise from future studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the characterization of the SNF1-AMPK pathway in nonconventional stress-resistant yeasts, like Zygosaccharomyces rouxii, Debaryomyces hansenii or Torulaspora delbrueckii, has received little attention. T. delbrueckii, a facultative fermentative species, has been recognized as the most promising alternative to industrial strains of S. cerevisiae (Hernández-López et al, 2003;Alves-Araújo et al, 2007), due to its high resistance to several types of stresses (Almeida and Pais, 1996;Hernández-López et al, 2003;Alves-Araújo et al, 2004). Genes like TdHOG1 (Hernández-López et al, 2006a) and TdCRZ1 (Hernández-López et al, 2006b), implicated in salt and osmotic stress in this yeast, have been identified and characterized.…”
Section: Introductionmentioning
confidence: 99%